Kadarsting module increase knowledge and practice of stunting toddlers’ family - Novita Ika Wardani; Lulut Handayani; Dhias Widiastuti (Poltekkes Kemenkes Yogyakarta, 2020)
Stunting is one of the Sustainable Development Goals (SDGs) targets to eliminating hunger and all forms of malnutrition in 2030. Stunting problems are mainly due to the influence of family parenting. Lack of family knowledge in providing care for stunting toddlers can worsen the situation of toddlers. The purpose of this study was to determine the effectiveness of the content module on the knowledge and practice of stunting toddler family management. Method: quasi experimental with a total sample of 30 control groups and 30 treatment group respondents. Educational provision to the treatment group was given for 2 days where respondents were given an explanation of the content of the staging module and on day 2 the mother was given a knowledge post test. For 3 months the mother will be observed about the module practice which is done every 2 weeks. There were differences in knowledge between the treatment (n=30; mean= 2.47) and control groups (n=30; mean= 1.10) with the result p=0.001. There were differences practice between the treatment (n=30; mean rank= 35.63) and control groups (n=30; mean rank= 25.37) with the result p=0.004. Kadarsting module was effective in increasing the knowledge and practice of mothers or families to deal with toddler stunting.